User Requirements Analysis for Government’s Budget Information System Using Kano’s Model - Al Ghozali, Isnen Hadi; Fathin, Muhammad Askar; Handoko, Andy Rio (Fakultas Ilmu Komputer, 2025)
This study finds out what attributes still require attention based on Kano’s Model analysis, which has to be used to prioritize software requirements in the government's or agency’s budget software. This research prioritizes software requirement attributes using Kano's Model. This research used an application by INTRAC as the basis for preparing a questionnaire distributed to 75 civil servants. From this research, it can be concluded that there are 15 sub-elements (including 25 features) classified as one-dimensional and four sub-elements (including eight features) classified as Indifferent. According to the Blauth Formula and continuous data analysis, the result shows a one-dimensional pattern. Based on the CS Coefficient, nine features are prioritized for development (especially the process budget revision). Development on the dimensions of interface requirements and functional requirements has the potential to increase the end user's satisfaction.